1983
DOI: 10.1128/aem.45.1.275-283.1983
|View full text |Cite
|
Sign up to set email alerts
|

Ecological relationships between Vibrio cholerae and planktonic crustacean copepods

Abstract: Strains of Vibrio cholerae, both O1 and non-O1 serovars, were found to attach to the surfaces of live copepods maintained in natural water samples collected from the Chesapeake Bay and Bangladesh environs. The specificity of attachment of V. cholerae to live copepods was confirmed by scanning electron microscopy, which revealed that the oral region and egg sac were the most heavily colonized areas of the copepods. In addition, survival of V. cholerae in water was extended in the presence of live copepods. Atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
305
2
11

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 628 publications
(329 citation statements)
references
References 25 publications
11
305
2
11
Order By: Relevance
“…Mourino-Perez et al, 2003;Thompson et al, 2004b;Hsieh et al, 2007). Several studies have shown that Vibrio spp., in particular V. cholerae, have the ability to colonize particles such as zooplankton and phytoplankton (Huq et al, 1983;Tamplin et al, 1990;Montanari et al, 1999). Potentially, eutrophication caused by nutrient loading could have a small but significant impact on Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…Mourino-Perez et al, 2003;Thompson et al, 2004b;Hsieh et al, 2007). Several studies have shown that Vibrio spp., in particular V. cholerae, have the ability to colonize particles such as zooplankton and phytoplankton (Huq et al, 1983;Tamplin et al, 1990;Montanari et al, 1999). Potentially, eutrophication caused by nutrient loading could have a small but significant impact on Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…The situation worsened in July, as the weekly incidence of cholera increased simultaneously in the four countries, reaching a peak in August or September, depending on the affected nation. The worst 7 days occurred during the 37th epidemic week (13)(14)(15)(16)(17)(18)(19), with almost 7000 new cases recorded altogether in the four countries. Thereafter, the epidemic extended beyond national borders, with the epidemic macro-centre being by the lakeside districts of Lake Chad [23] (Fig.…”
Section: Cholera In the Lake Chad Basinmentioning
confidence: 99%
“…MED222 with a similarity of 64-69% conserved amino acids. Indeed, some bacteria of the Vibrionaceae family are well known to associate to marine arthropods, for example, copepods (Huq et al, 1983), possibly indicating a role for the marine ymt genes in this context.…”
Section: Yersinia Phospholipase-related Toxinmentioning
confidence: 99%